2009
DOI: 10.1159/000235686
|View full text |Cite
|
Sign up to set email alerts
|

<i>KLOTHO</i> Gene Polymorphisms G-395A and C1818T Are Associated with Low-Density Lipoprotein Cholesterol and Uric Acid in Japanese Hemodialysis Patients

Abstract: Background/Aims: This study aimed to investigate the association of the KLOTHO gene single nucleotide polymorphisms (SNPs), G-395A and C1818T, with various laboratory data in 219 Japanese hemodialysis (HD) patients. Methods: The genotyping of G-395A in the promoter region and C1818T in exon 4 was performed using polymerase chain reaction with confronting two-pair primers (PCR-CTPP) assay. Results: In HD patients, the allele frequencies of G-395A were 0.847 for the G allele and 0.153 for the A allele and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…GWAS have revealed more common alterations in KL that do not cause overt and disabling disease but do affect disease risk. Two of these variants, G395A in the promoter region and C1818T in exon 4 of KL, are associated with increased risk of cardiovascular disease, priapism, nephropathy, osteoarthritis, diabetes, and increased bone mineral density (41)(42)(43)(44)(45)(46)(47)(48)(49). Multiple studies have also shown an association of KLVS with both longevity and disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have revealed more common alterations in KL that do not cause overt and disabling disease but do affect disease risk. Two of these variants, G395A in the promoter region and C1818T in exon 4 of KL, are associated with increased risk of cardiovascular disease, priapism, nephropathy, osteoarthritis, diabetes, and increased bone mineral density (41)(42)(43)(44)(45)(46)(47)(48)(49). Multiple studies have also shown an association of KLVS with both longevity and disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho gene is also known to have some anti-aging and antiatherosclerosis properties [4,5]. Klotho gene polymorphism has been shown to be associated with the severity of renal failure and aging parameters such as common carotid artery intima media thickness, low density lipoprotein and uric acid levels in CKD patients [6][7][8] . Klotho gene mutations may cause early dysfunction and thrombosis of vascular accesses in haemodialysis patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Klotho geninin bazı yaş-lanmayı engelleyici ve aterosklerozu önleyici özelliklerinin olduğu bilinmketedir (8)(9)(10). Klotho gen polimorfizminin KBH hastalarında böbrek yetmezliğinin şiddeti ve karotid arter intima media kalınlığı, düşük dansiteli lipoprotein ve ürik asid düzeyleri gibi yaşlanma belirteçleriyle ilişkili olduğu gösteril-miştir (11)(12)(13). Klotho gen mutasyonları hemodiyaliz hastalarının damar giriş yollarında erken disfonksiyon ve tromboza neden olabilirler (14).…”
Section: Introductionunclassified